Effects of anodizing conditions and the addition of Al2O3/PTFE particles on the microstructure and the mechanical properties of porous anodic coatings on the AA1050 aluminium alloy - Remešová, Michaela; Tkachenko, Serhii; Kvarda, Daniel; Ročńáková, Ivana; Gollas, Bernhard; Menelaou, Melita; Čelko, Ladislav; Kaiser, Jozef (My University, 2020)
In the present study, porous anodic aluminium oxide (AAO) coatings with and without particles of Al2O3 (aluminium oxide) and polytetrafluorethylene (PTFE) were produced on AA1050 aluminium alloy via galvanostatic anodizing in acidic electrolyte. The effects of anodizing conditions (i.e. temperature, current density and composition of electrolyte) on the morphology, thickness, and microhardness were studied via scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDX) and Vickers hardness tester. The results showed that the decrease of electrolyte temperature from 24 to 10 °C and the addition of 20 g/L oxalic acid to 15% H2SO4 electrolyte led to the formation of thicker (34 µm) and harder porous AAO coating with hillocks. Furthermore, the decrease of applied current density from 3 to 1 A/dm2 resulted in the formation of thinner coating (10 µm) without hillocks. The intermetallic phases based on Al-Fe and Al-Fe-Si compounds present in AA1050 alloy were not preferably dissoluted during the anodizing process at 10 °C of electrolyte. The tribological properties of the anodic coatings were investigated by the dry friction test. The results showed that the addition of Al2O3 and PTFE particles to sulfuric-oxalic acid electrolyte resulted in hard anodic composite coatings with enhanced wear resistance.
Keywords: Anodizing; AA1050; Coating microstructure; Hillocks; Wear